Correlation Between Pre-Chemotherapy AMH Level, Menstrual Status, and Prediction of Ovarian Function Recovery after FAC Chemotherapy AMH in Breast Cancer Patients (Majalah Kedokteran Bandung, 2023)
Around 52.6% of women aged
Keywords: Anti-Mullerian hormone; breast neoplasms; chemotherapy